Question
upstudy study bank question image url

9. \( \begin{aligned} \frac{1}{x}+\frac{1}{y}+\frac{1}{z} & =5 \\ \frac{1}{x}+\frac{1}{y} & =2 \\ \frac{1}{x}-\frac{1}{z} & =-2\end{aligned} \)

Ask by Mcfarlane Vaughn. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( x = 1 \), \( y = 1 \), \( z = \frac{1}{3} \)

Solution

To solve the system of equations: \[ \begin{aligned} \frac{1}{x} + \frac{1}{y} + \frac{1}{z} &= 5 \quad \text{(1)} \\ \frac{1}{x} + \frac{1}{y} &= 2 \quad \text{(2)} \\ \frac{1}{x} - \frac{1}{z} &= -2 \quad \text{(3)} \end{aligned} \] Let's introduce substitution variables to simplify the equations: \[ a = \frac{1}{x}, \quad b = \frac{1}{y}, \quad c = \frac{1}{z} \] Substituting these into the original system, we get: \[ \begin{aligned} a + b + c &= 5 \quad \text{(1')} \\ a + b &= 2 \quad \text{(2')} \\ a - c &= -2 \quad \text{(3')} \end{aligned} \] **Step 1:** Subtract equation (2') from equation (1') to find \( c \): \[ (a + b + c) - (a + b) = 5 - 2 \\ c = 3 \] **Step 2:** Substitute \( c = 3 \) into equation (3') to find \( a \): \[ a - 3 = -2 \\ a = 1 \] **Step 3:** Substitute \( a = 1 \) into equation (2') to find \( b \): \[ 1 + b = 2 \\ b = 1 \] **Step 4:** Now, convert back to the original variables using \( a = \frac{1}{x}, b = \frac{1}{y}, \) and \( c = \frac{1}{z} \): \[ \frac{1}{x} = 1 \quad \Rightarrow \quad x = 1 \\ \frac{1}{y} = 1 \quad \Rightarrow \quad y = 1 \\ \frac{1}{z} = 3 \quad \Rightarrow \quad z = \frac{1}{3} \] **Solution:** \[ x = 1, \quad y = 1, \quad z = \frac{1}{3} \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To solve the system of equations, we can first express the variables in terms of their reciprocals. Let's define \( a = \frac{1}{x} \), \( b = \frac{1}{y} \), and \( c = \frac{1}{z} \). Rewriting the equations in terms of \( a, b, c \) gives us: 1. \( a + b + c = 5 \) 2. \( a + b = 2 \) 3. \( a - c = -2 \) From the second equation, we can express \( c \): \[ c = 5 - (a + b) \] Substituting \( a + b = 2 \) into the expression gives: \[ c = 5 - 2 = 3 \] Now substituting \( c = 3 \) into the third equation: \[ a - 3 = -2 \] This simplifies to: \[ a = 1 \] Now that we have \( a = 1 \) and \( b = 2 - a = 2 - 1 = 1 \), we know: \[ 1 = \frac{1}{x} \Rightarrow x = 1 \\ 1 = \frac{1}{y} \Rightarrow y = 1 \\ 3 = \frac{1}{z} \Rightarrow z = \frac{1}{3} \] Thus, the solutions are: \[ x = 1, \quad y = 1, \quad z = \frac{1}{3} \] So the final answer is: \((x, y, z) = \left(1, 1, \frac{1}{3}\right)\)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy